Imaging of aortic arch anomalies and associated findings. (December 2012) - Londono-Obregon, Camila; Fogel, Mark
Imaging is important in the diagnosis of aortic arch disease. Echocardiography is the test of choice. It possess minimal risk, can be performed at the bedside without sedation and provides a complete evaluation of the heart and the great vessels. Cardiac magnetic resonance imaging (cMRI) is an alternative when echocardiography is limited by acoustic windows. It does not use ionizing radiation or nephrotoxic contrast. 3D reconstruction and soft tissue characterization are possible. cMRI evaluates physiology and may be an alternative to diagnostic catheterization. Longer scan times, need for sedation and the presence of implantable metal devices that may be a contraindication for cMRI are the main limiting factors. Computed tomography with angiography has very short scanning times, limiting the need for sedation. It has high spatial resolution and can evaluate physiology. Its use is limited because it uses radiation, has poor temporal resolution compared with cMRI and uses iodinated contrast. Catheterization is the test of choice, and can serve for diagnostic and therapeutic purposes.